Molecular methods for identification of clostridium tetani by targeting neurotoxin - Dharne, Mahesh S.; Nagoba, Basavraj S.; Gohil, Kushal N. (Methods Molecular Biology, 2017)
Tetanus is a potentially fatal muscle spasm disease. It is an important public health problem, especially in rural/tribal areas of developing countries. Tetanus toxin, a neurotoxin (tetanospasmin ), is the most important virulence factor that plays a key role in the pathogenicity of tetanus . Confirmation of virulence by confirming the production of tetanospasmin by infecting species forms the most important part in the diagnosis of tetanus . Various molecular methods have been devised for confirmation of diagnosis by targeting different genes. The most common molecular methods are tetanospasmin producing (TetX) gene-targeted methods using TetX-specific primers. Here, we describe various molecular methods targeting TetX gene such as polymerase chain reaction, pulsed-field gel electrophoresis, Southern blotting, loop-mediated isothermal amplification assay, etc. to confirm the virulence of Cl. tetani.

Metagenomic insights to understand transient influence of Yamuna River on taxonomic and functional aspects of bacterial and archaeal communities of River Ganges - Samson, Rachel; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Rajput, Vinay; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Science of the Total Environment, 2019)
River confluences are interesting ecosystems to investigate for their microbial community structure and functional potentials. River Ganges is one of the most important and holy river of India with great mythological history and religious significance. The Yamuna River meets Ganges at the Prayagraj (formerly known as Allahabad), India to form a unique confluence. The influence of Yamuna River on taxonomic and functional aspects of microbiome at this confluence and its downstream, remains unexplored. To unveil this dearth, whole metagenome sequencing of the microbial (bacterial and archaeal) community from the sediment samples of December 2017 sampling expedition was executed using high throughput MinION technology. Results revealed differences in the relative abundance of bacterial and archaeal communities across the confluence. Grouped by the confluence, a higher abundance of Proteobacteria and lower abundance of Bacteroidetes and Firnacutes was observed for Yamuna River (G15Y) and at immediate downstream of confluence of Ganges (G15DS), as compared to the upstream, confluence, and farther downstream of confluence. A similar trend was observed for archaeal communities with a higher abundance of Euryarchaeoto in G15Y and G15DS, indicating Yamuna River's influence. Functional gene(s) analysis revealed the influence of Yamuna River on xenobiotic degradation, resistance to toxic compounds, and antibiotic resistance interceded by the autochthonous microbes at the confluence and succeeding downstream locations. Overall, similar taxonomic and functional profiles of microbial communities before confluence (upstream of Ganges) and farther downstream of confluence, suggested a transient influence of Yamuna River. Our study is significant since it may be foundational basis to understand impact of Yamuna River and also rare event of mass bathing on the microbiome of River Ganges. Further investigation would be required to understand, the underlying cause behind the restoration of microbial profiles post-confluence farther zone, to unravel the rejuvenation aspects of this unique ecosystem. (C) 2019 Elsevier B.A. All rights reserved.
Keywords: Confluence zone; Ganges; Metagenomics; Transient influence; Yamuna

Metabolic engineering and synthetic biology for isoprenoid production in Escherichia coli and Saccharomyces cerevisiae - Navale, Govinda R.; Dharne, Mahesh S.; Shinde, Sandip S. (Applied Microbiology and Biotechnology, 2021)
Isoprenoids, often called terpenoids, are the most abundant and highly diverse family of natural organic compounds. In plants, they play a distinct role in the form of photosynthetic pigments, hormones, electron carrier, structural components of membrane, and defence. Many isoprenoids have useful applications in the pharmaceutical, nutraceutical, and chemical industries. They are synthesized by various isoprenoid synthase enzymes by several consecutive steps. Recent advancement in metabolic engineering and synthetic biology has enabled the production of these isoprenoids in the heterologous host systems like Escherichia coli and Saccharomyces cerevisiae. Both heterologous systems have been engineered for large-scale production of value-added isoprenoids. This review article will provide the detailed description of various approaches used for engineering of methyl-d-erythritol-4-phosphate (MEP) and mevalonate (MVA) pathway for synthesizing isoprene units (C-5) and ultimate production of diverse isoprenoids. The review particularly highlighted the efforts taken for the production of C-5-C-20 isoprenoids by metabolic engineering techniques in E. coli and S. cerevisiae over a decade. The challenges and strategies are also discussed in detail for scale-up and engineering of isoprenoids in the heterologous host systems.
Keywords: Escherichia coli; Isoprenoids; Metabolic engineering; Saccharomyces cerevisiae; synthetic biology

Metagenomic analysis reveals genetic insights on biogeochemical cycling, xenobiotic degradation, and stress resistance in mudflat microbiome - Mohapatra, Madhusmita; Yadav, Rakeshkumar; Rajput, Vinay; Dharne, Mahesh S.; Rastogi, Gurdeep (Journal of Environmental Management, 2021)
<span style="color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Mudflats are highly productive coastal ecosystems that are dominated by halophytic vegetation. In this study, the mudflat sediment microbiome was investigated from Nalabana Island, located in a brackish water coastal wetland of India; Chilika, based on the MinION shotgun metagenomic analysis. Bacterial, archaeal, and fungal communities were mostly composed of Proteobacteria (38.3%), Actinobacteria (20.7%), Euryarchaeota (76.1%), Candidatus Bathyarchaeota (6.8%), Ascomycota (47.2%), and Basidiomycota (22.0%). Bacterial and archaeal community composition differed significantly between vegetated mudflat and un-vegetated bulk sediments. Carbon, nitrogen, sulfur metabolisms, oxidative phosphorylation, and xenobiotic biodegradation were the most common microbial functionalities in the mudflat metagenomes. Furthermore, genes involved in oxidative stresses, osmotolerance, secondary metabolite synthesis, and extracellular polymeric substance synthesis revealed adaptive mechanisms of the microbiome in mudflat habitat. Mudflat metagenome also revealed genes involved in the plant growth and development, suggesting that microbial communities could aid halophytic vegetation by providing tolerance to the abiotic stresses in a harsh mudflat environment. Canonical correspondence analysis and co-occurrence network revealed that both biotic (vegetation and microbial interactions) and abiotic factors played important role in shaping the mudflat microbiome composition. Among abiotic factors, pH accounted for the highest variance (20.10%) followed by available phosphorus (19.73%), total organic carbon (9.94%), salinity (8.28%), sediment texture (sand) (6.37%) and available nitrogen (5.53%) in the mudflat microbial communities. Overall, this first metagenomic study provided a comprehensive insight on the community structure, potential ecological interactions, and genetic potential of the mudflat microbiome in context to the cycling of organic matter, xenobiotic biodegradation, stress resistance, and in providing the ecological fitness to halophytes. These ecosystem services of the mudflat microbiome must be considered in the conservation and management plan of coastal wetlands. This study also advanced our understanding of fungal diversity which is understudied from the coastal lagoon ecosystems.

Metagenomic exploration reveals a differential patterning of antibiotic resistance genes in urban and peri-urban stretches of a riverine system - Rajput, Vinay; Yadav, Rakeshkumar; Dharne, Mahesh S. (Environmental Science and Pollution Research, 2021)
{Antimicrobial resistance in the riverine ecosystem of urban areas is an alarming concern worldwide, indicating the importance of molecular monitoring to understand their patterning in urban and peri-urban areas. In the present study, we evaluated the influence of urban rivers on the connected peri-urban rivers of a riverine system of India in the context of antibiotic resistance genes. The rivers traversing through urban (Mula, Mutha, Pawana, and Ramnadi) and peri-urban stretches (Bhima and Indrayani) form the riverine system of Pune district in Maharashtra, India. The MinION-based shotgun metagenomic analysis revealed the resistome against 26 classes of antibiotics, including the last line of antibiotics. In total, we observed 278 ARG subtypes conferring resistance against multiple drugs (40%), bacitracin (10%), aminoglycoside (7.5%), tetracycline (7%), and glycopeptide (5%). Further, the alpha diversity analysis suggested relatively higher ARG diversity in the urban stretches than peri-urban stretches of the riverine system. The NMDS (non-metric multidimensional scaling) analysis revealed significant differences with overlapping similarities (stress value = 0.14
Keywords: Antibiotic resistance; MinION; Peri-urban rivers; Urbanization